Upaya Kementrian Perdagangan dalam Bernegosiasi melalui Instagram terhadap Kenaikan Harga Minyak Goreng bagi Konsumen - Prayogi Adie Pradja (Program Studi Hubungan Masyarakat Politeknik LP3I, 2022)
ABSTRACT This study aims to determine consumers who still consume cooking oil. The research method that the researcher has done is using a quantitative method. The population in this study are consumers in Indonesia. Analysis and data collection was done by filling out a questionnaire via google. The results of this study stated that as many as 89.8% of 59 respondents stated that it was very influential that the increase in cooking oil prices was very influential in daily life for consumers, as many as 86.4% of 59 respondents stated that it was very helpful that the efforts of the ministry of trade regarding policy one price of Rp.14,000 per liter of cooking oil, 64.4% of 59 respondents said it was very appropriate in the government's efforts to handle the increase in cooking oil prices, as many as 55.9% of 59 respondents said it was very appropriate regarding the efforts of the ministry of trade to carry out negotiations and communication through social media Instagram.